Esperança, espiritualidade e resiliência de familiares no contexto da dependência de substâncias psicoativas: estudo correlacional - Lima, Nathalya Ferreira (Universidade Federal de São Carlos, 2021)
The family that experiences the context of chemical dependency suffers negative impacts on their functionality. In the process of facing this adverse situation, family members of drug users seek resources to maintain hope in the drug user relative's recovery process through spirituality. This study analyzed the relationship between hope, spirituality and resilience of family members of psychoactive substance users undergoing treatment or not. The research method consists of a correlational, cross-sectional study with a quantitative approach, with a sample of eighty-one family members of psychoactive substance users undergoing treatment or not in Primary and Specialized Care services in a city in the interior of the State of São Paulo. The data collection instruments consisted of the Herth Hope Scale, the Pinto and Pais-Ribeiro Spirituality Scale and the Wagnil and Young Resilience Scale. The analysis was performed using descriptive and inferential statistics. This study was approved by the Ethics Committee for Research with Human Beings at UFSCar, under opinion n.2,878,696, on 06/06/2018. Due to the COVID-19 pandemic, the project needed to be amended, and was sent to the Ethics Committee for Research with Human Beings at UFSCar, for continuation of the research by electronic/virtual means, according to Ordinance GR No. 4380, of 20/03/ 2020, which provides for the extension of suspension of classes, curricular activities and temporary measures, aiming to reduce personal exposure and face-to-face interactions between members of the UFSCar community. The results confirmed the hypotheses of the present study, that is, that there is a positive correlation between the strengths of hope and spirituality, and the higher these strengths, the greater the resilience of this family member. There were no significant differences regarding the correlation between hope, spirituality and resilience in the results of family members of different ages and sex, as well as whether the user of psychoactive substances would undergo any treatment or not, and regarding their consumption. Regarding these strengths in family members who participate or not in a family group, there was also no significant difference in the results. Conclusion: all forces had good results, that is, family members of psychoactive substance users have good hope, good spirituality and good resilience.
Hope, spirituality and resilience of families in the context of dependence on psychoactive substance: correlational study
Keywords: Esperança; Espiritualidade; Resiliência psicológica; Família; Transtornos relacionados ao uso de substâncias; Hope; Spirituality; Resilience Psychological; Family; Substance-Related Disorders; CIENCIAS DA SAUDE::ENFERMAGEM